Molecular dynamics study of pressure effect on glass formation and the crystallization in liquid CuNi alloy - Kazanc, S. (Elsevier Science Bv, 2006)
The cooling rate and pressure are two critical factors affecting the resulting structure of a liquid-solid transition. The pressure effect on the rapid solidification of liquid CuNi alloys is studied by using molecular dynamic simulation method. To model the interactions between atoms Sutton-Chen type of embedded atom method based on many-body interaction were used. Radial distribution function (RDF), the changes of volume and Wendt-Abraham parameters were calculated to determine temperatures of glass and crystal formation for model alloy system under different pressures. Crystal and amorphous transitions for different pressures were formed at cooling rate of 4 x 10(12) and 4 x 10(13) K/s, respectively. It is observed that the increase of pressure causes in increase of glass and crystal formation temperatures. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: embedded atom method; rapid solidification; molecular dynamics simulation; CuNi alloys